Shaping Medieval Markets: The Organisation of Commodity Markets in Holland, c. 1200–c. 1450 - Jessica Dijkman (Brill, 2011)
The late Middle Ages witnessed the transformation of the county of Holland from a peripheral agrarian region to a highly commercialised and urbanised one. This book examines how the organisation of commodity markets contributed to this remarkable development. Comparing Holland to England and Flanders, the book shows that Holland's specific history of reclamation and settlement had given rise to a favourable balance of powers between state, nobility, towns and rural communities that reduced opportunities for rent-seeking and favoured the rise of efficient markets. This allowed burghers, peasants and fishermen to take full advantage of new opportunities presented by changing economic and ecological circumstances in the late fourteenth and early fifteenth centuries.
Keywords: 330; Holland; Middle Ages; Economic history; Institutions; Markets; Markt; Marktmechanismus; Marktintegration; Rechtsdurchsetzung; Mittelalter; Wirtschaftsgeschichte; Niederlande